2015
DOI: 10.2174/1389202916666150313230812
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Scanning and Characterization of Sorghum bicolor L. Heat Shock Transcription Factors

Abstract: A genome-wide scanning of Sorghum bicolor resulted in the identification of 25 SbHsf genes. Phylogenetic analysis shows the ortholog genes that are clustered with only rice, representing a common ancestor. Promoter analysis revealed the identification of different cis-acting elements that are responsible for abiotic as well as biotic stresses. Hsf domains like DBD, NLS, NES, and AHA have been analyzed for their sequence similarity and functional characterization. Tissue specific expression patterns of Hsfs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 65 publications
3
25
0
Order By: Relevance
“…The first HSF gene found in plants was cloned in tomato (Solanum lycopersicum) [12] and the HSF gene family have now been characterized in Arabidopsis (Arabidopsis thaliana), rice (Oryza sativa) [13], maize (Zea mays) [14], soybean (Glycine max) [15], chickpea (Cicer arietinum) [16], and sorghum (Sorghum bicolor) [17], as well as in vegetables including Chinese cabbage (Brassica rapa) [18] and pepper (Capsicum annuum) [19], and fruits such as apple (Malus domestica) [20] and pear (Pyrus bretschneideri) [21]. In addition to the Hsf s involved in the regulation of heat-resistance mechanism studied in Arabidopsis [22,23], many Hsfs have been found to participate in other responses in various plant species in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The first HSF gene found in plants was cloned in tomato (Solanum lycopersicum) [12] and the HSF gene family have now been characterized in Arabidopsis (Arabidopsis thaliana), rice (Oryza sativa) [13], maize (Zea mays) [14], soybean (Glycine max) [15], chickpea (Cicer arietinum) [16], and sorghum (Sorghum bicolor) [17], as well as in vegetables including Chinese cabbage (Brassica rapa) [18] and pepper (Capsicum annuum) [19], and fruits such as apple (Malus domestica) [20] and pear (Pyrus bretschneideri) [21]. In addition to the Hsf s involved in the regulation of heat-resistance mechanism studied in Arabidopsis [22,23], many Hsfs have been found to participate in other responses in various plant species in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that the most Hsfs was clustered into A branches followed by B branches, and the least was C branches. Meanwhile, they concluded that the difference between the three species of Hsfs in the A and B branches lead to the different responses of different species to stress [14]. Therefore, the results in this research work suggested that the different stress-tolerant ability between wild and cultivated rice might be induced by the difference of Hsfs between 6 wild rice and cultivated rice on the evolutionary branches.…”
Section: Discussionmentioning
confidence: 70%
“…But the number of China pear Hsf A branch was 19, while B and C branch Hsfs were 8 and 2. Nagaraju et al used the same strategy to build the evolutionary tree of rice, Arabidopsis and sorghum Hsfs [14]. They also found that the most Hsfs was clustered into A branches followed by B branches, and the least was C branches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first HSF gene in plants was cloned in tomato (Solanum lycopersicum L.) [11] and they have now been characterized in Arabidopsis, rice [12], maize (Zea mays L.) [13], soybean (Glycine max L.) [14], chickpea [15], and sorghum [16], as well as in vegetables including Chinese cabbage [17] and pepper [18], and fruits such as apple [19] and pear [20]. In addition to those Hsfs who involved in the regulation of heat-resistance mechanisms were researched in Arabidopsis [21,22], many Hsfs have been found to be participate in other response in various plants in recent years.…”
Section: Introductionmentioning
confidence: 99%